PENGARUH PENYULUHAN KESEHATAN LINGKUNGAN TERHADAP TINGKAT PENGETAHUAN DAN PELAKSANAAN KESEHATAN LINGKUNGAN SMP NEGERI TAMBAKSARI KECAMATAN TAMBAKSARI KABUPATEN CIAMIS - Hermawan, Yoni (Bumi Lestari Journal of Environment, 2013)
Abstrak Healthy behaviors at school showed unsatisfactory result, this can be seen from the result of quick survey conducted in 2009 in the regency of Ciamis which shows: PHBS School level I: 40,8%, PHBS School Level II: 33,3%, PHBS School Level 3: 20,5% and PHBS school Level IV: 5,4%. From the result of the survey, behavioral problems are found: 83,7% students smoke, 63,6 students have not been exercising regularly, whereas environmental issues include: Schools that haven’t owned latrines 63%, schools that haven’t managed their wastes properly: 62%, and schools that haven’t had sewers:68%, the influence of environmental health education to the level of students’ knowledge and implementation of environmental health at one of the Junior High School at Tambaksari, CIamis District in 2011. The research method is experimental method with pretest and post test approach. The result shows that before counseled, the student’s knowledge are largely categorized as adequate, that is 56 students (66,7%) and after they were given the counseling, the student’s knowledge largely categorized as decent, that is 51 students (60,7%). Based on the T-Test result, the value of ñ is 0,000, so it can be concluded that there was influence of the environmental counseling on the level of knowledge in one of the Junior High School in Tambaksari, CIamis District in the year of 2011 because the value of á is higher than ñ (á > ñ) (0,05 > 0,000). The implementation of environmental health before the counseling are given mostly are categorized as negative that is as many as 62 people (73,8%) and after being given the counseling, student’s knowledge mostly categorized as positive that is 55 people (65,5%). Based on the T-Test result, the value of ñ is 0,000, so it can be concluded that there was influence of the environmental counseling on the level of knowledge in one of the Junior High School in Tambaksari, CIamis District in the year of 2011 because the value of á is higher than ñ (á > ñ) (0,05 > 0,000), the result of the test results of the study of the influence of environmental health education on the level of students’ knowledge and implementation of environmental health at one of the Junior High School in Tambaksari, CIamis District in the year 2011.
Keywords: Keywords : counseling, knowledge, environmental health